2022
DOI: 10.31729/jnma.7235
|View full text |Cite
|
Sign up to set email alerts
|

Depression, Anxiety and Stress among Nurses Providing Care to the COVID-19 Patients: A Descriptive Cross-sectional Study

Abstract: Introduction: Addressing adequately the mental health during and after COVID-19, as well as preparation for possible future outbreaks, requires an understanding of the nature and extent of mental health impacts, factors related to negative mental health outcomes and symptoms of mental illness. The aim of this study was to find the prevalence of depression, anxiety and stress among nurses providing care to the COVID-19 patients. Methods: A descriptive cross-sectional study was conducted from 10th April 2021 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
0
9
0
1
Order By: Relevance
“…For example, the Brasil study by Michele Mandagará de Oliveira et al (2022) described higher prevalence of depression, anxiety, sleep disorders, and minor psychiatric disorders [ 2 ]. Bhandari et al (2022), in their study, confirmed a similar result: a higher prevalence of depression, anxiety, and stress among 301 nurses in Nepal [ 3 ]. The research by Lai et al (2020) demonstrated the existence of high fear, anxiety, and sleep deprivation in a group of healthcare employees [ 4 ].…”
Section: Introductionmentioning
confidence: 53%
“…For example, the Brasil study by Michele Mandagará de Oliveira et al (2022) described higher prevalence of depression, anxiety, sleep disorders, and minor psychiatric disorders [ 2 ]. Bhandari et al (2022), in their study, confirmed a similar result: a higher prevalence of depression, anxiety, and stress among 301 nurses in Nepal [ 3 ]. The research by Lai et al (2020) demonstrated the existence of high fear, anxiety, and sleep deprivation in a group of healthcare employees [ 4 ].…”
Section: Introductionmentioning
confidence: 53%
“…Among nurses, a related study conducted by Bhandari et al. on 301 nursing staff in Nepal showed that 85.72% of them were depressed, 62.80% experienced anxiety, and 49.84% stress ( 46 ). Moreover, Kaushik et al.…”
Section: Discussionmentioning
confidence: 99%
“…Most of previous studies on anxiety and depression in Nepal are confined to specific group of participants like health care workers during COVID-19 pandemic 10,11 , nurses 12,13 , traffic police 14 , among patients of type II diabetes 15,16 , people living in quarantine centre during COVID-19 pandemic 45 , patients of MDR TB 17 and hypertensive adults 18 and are confined in specific localities. However, our study involves an analysis from nationally representative sample taking into consideration the current federal structure.…”
Section: Strengths and Limitations Of The Studymentioning
confidence: 99%
“…1,9 Approximately, 99% of mental health studies are funded by high income countries and only 5% of total mental health research finding go in LMICs 1, 9 like Nepal. Although there are some studies anxiety and depression in Nepal, they are mostly confined in specific geographic area and among specific group of people like health care workers [10][11][12][13] , traffic police 14 , among patients with specific disease conditions [15][16][17][18] specific geographic area.…”
Section: Introductionmentioning
confidence: 99%